2020
DOI: 10.15252/embj.2019102731
|View full text |Cite
|
Sign up to set email alerts
|

CLUH granules coordinate translation of mitochondrial proteins with mTORC1 signaling and mitophagy

Abstract: Mitochondria house anabolic and catabolic processes that must be balanced and adjusted to meet cellular demands. The RNAbinding protein CLUH (clustered mitochondria homolog) binds mRNAs of nuclear-encoded mitochondrial proteins and is highly expressed in the liver, where it regulates metabolic plasticity.Here, we show that in primary hepatocytes, CLUH coalesces in specific ribonucleoprotein particles that define the translational fate of target mRNAs, such as Pcx, Hadha, and Hmgcs2, to match nutrient availabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
64
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(71 citation statements)
references
References 74 publications
5
64
2
Order By: Relevance
“…During this process, intermediates produced from the mitochondrial metabolism can be used as raw materials for anabolism and signal molecules that regulate cell activity [4]. Increasing numbers of studies are providing evidence to validate the claim that the metabolic activities and functions of mitochondria are triggered by extracellular environmental alterations [5][6][7][8]. The environmental alterations include oxygen, temperature, nutrients, endocrine, toxicity and other cellular stress-induced factors [5][6][7][8].…”
Section: Mitochondrial Stress Responsementioning
confidence: 99%
“…During this process, intermediates produced from the mitochondrial metabolism can be used as raw materials for anabolism and signal molecules that regulate cell activity [4]. Increasing numbers of studies are providing evidence to validate the claim that the metabolic activities and functions of mitochondria are triggered by extracellular environmental alterations [5][6][7][8]. The environmental alterations include oxygen, temperature, nutrients, endocrine, toxicity and other cellular stress-induced factors [5][6][7][8].…”
Section: Mitochondrial Stress Responsementioning
confidence: 99%
“…Hence, a coordination between translational control and metabolic output ultimately involving mitochondrial respiratory functions is expected to contribute to cell homeostasis and fitness 19,20 . However, relatively few proteins and pathways have been established to exert a direct role in balancing cytoplasmic translation initiation with mitochondrial metabolism 21,22 . eIF6 represents a significant example, as it has been clearly shown that it negatively controls 80S monosome assembly, a necessary step for translation initiation, while at the same time playing a critical positive role in mitochondrial functions, as revealed by broad changes in the mitochondrial proteome in eIF6 hemizygous mice [23][24][25] .…”
Section: Discussionmentioning
confidence: 99%
“…The role of Smaug orthologues as post-transcriptional regulators of energetic metabolism appears evolutionary conserved as yeast Vts1p –which forms MLOs and prion-like condensates– controls mRNAs linked to nutrient sensing (Chakravarty et al, 2020; She et al, 2017). Translation of nuclear-encoded transcripts at the mitochondrial periphery is known to be regulated by a reduced number of RNA-binding proteins, including the highly conserved factors clustered mitochondria homolog (CLUH) and Pumilio orthologs (reviewed in(D’Amico et al, 2019; Gao et al, 2014; Gehrke et al, 2015; Kopp et al, 2019; Lee & Tu, 2015; Olivas & Parker, 2000; Pla-Martin et al, 2020; Schatton et al, 2017; Schatton & Rugarli, 2018; Vardi-Oknin & Arava, 2019; Wakim et al, 2017) The putative interplay between these pathways and Smaug remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%